Adverse effects of obesity on cognitive functions in individuals at ultra high risk for bipolar disorder: Results from the global mood and brain science initiative. (11th May 2017) - McIntyre, Roger S.; Mansur, Rodrigo B.; Lee, Yena; Japiassú, Letícia; Chen, Kun; Lu, Rui; Lu, Weicong; Chen, Xiaodong; Li, Ting; Xu, Guiyun; Lin, Kangguang
Abstract : Background: The burden of illness associated with bipolar disorder (BD) warrants early pre‐emption/prevention. Prediction models limited to psychiatric phenomenology have insufficient predictive power. Herein, we aimed to evaluate whether the presence of overweight/obesity is associated with greater cognitive decline in individuals at high risk (HR) or ultra high risk (UHR) for BD. Methods: We conducted a retrospective analysis to investigate the moderational role of body mass index (BMI) on measures of cognitive function. Subjects between the ages of 8 and 28 years with a positive family history of BD were compared to age‐matched controls with a negative family history of BD. Subjects with at least one biological parent with bipolar I/II disorder were further stratified into UHR or HR status by the presence or absence, respectively, of subthreshold hypomanic, major depressive, attenuated psychotic, and/or attention‐deficit/hyperactivity disorder symptoms. Results: A total of 36 individuals at HR for BD, 33 individuals at UHR for BD, and 48 age‐matched controls were included in the analysis. Higher BMI was significantly associated with lower performance on measures of processing speed (i.e. Brief Assessment of Cognition in Schizophrenia−symbol coding: r =−.186, P =.047) and attention/vigilance (i.e. Continuous Performance Test−Identical Pairs: r =−.257, P =.006). There were trends for negative correlations between BMI and measures of working memory (i.e. Wechsler Memory Scale‐III Spatial Span: r =−0.177, P =.059) and overall cognitive function (i.e. Measurement and Treatment Research to Improve Cognition in Schizophrenia composite score: r =−.157, P =.097). Negative associations between BMI and cognitive performance were significantly stronger in the UHR group than in the HR group, when compared to controls. Conclusions: Individuals at varying degrees of risk for BD exhibit greater cognitive impairment as a function of co‐existing overweight/obesity. Prediction models for BD may be substantively informed by including information related to overweight/obesity and, perhaps, other general medical conditions that share pathology with BD. Our findings herein, as well as the salutary effects of bariatric surgery on measures of cognitive function in obese populations, provide the rationale for hypothesizing that mitigating excess weight in individuals at elevated risk for BD may forestall or prevent declaration of illness.